Lost Wooden Architecture of the Pacific Russia - Ivanova, Alina (project baikal, 2020)
The abundance and relative cheapness of the material provided ample possibilities for adaptation and experimentation with stylistics by volume-spatial forms of wooden buildings in Siberia and the Far East. At the same time, wooden architecture was at high risk of degradation and destruction. The article based on field research in various regions and detailed graphic reconstruction of several objects allows to form a more complete estimate of the development and preservation of wooden architecture in the Pacific Russia.